Single‐feed low‐profile resonant cavity antenna covering entire Ku‐band. Issue 9 (4th April 2016) - Hashmi, R.M.; Esselle, K.P.
Abstract : A simple single‐feed resonant cavity antenna having a flat, low‐profile all‐dielectric partially reflecting surface (PRS) is described, which has a wide 3 dB bandwidth covering the entire Ku‐band. The PRS is composed of three dielectric sections, forming a planar slab with the dielectric constant of the slab decreasing from the centre to the edge in three steps. In addition to the directivity enhancement (up to 10 dB over the feed antenna), it is shown that such single‐layer PRSs remarkably improve the bandwidth of RCAs while reducing the profile of the antenna significantly. The total height of the antenna prototype is only 0.65 λ 0 at the lowest operating frequency. Experimental results are included to validate the proposed concept.